Caracterização genotípica microrganismos isolados de infecções da corrente sanguína relacionadas a cateteres em recém-nascidos - Pazzini, Letícia Teixeira [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
As infecções relacionadas a cateteres constituem uma das principais causas de bacteremias em UTIs neonatais. O objetivo do presente estudo foi analisar por meio de técnicas de tipagem molecular a similaridade dos microrganismos isolados de cateteres e hemoculturas para o diagnóstico de infecção da corrente sanguínea relacionada com cateteres em recém-nascidos. Foram avaliadas 124 pontas de cateteres e 155 hemoculturas concomitantes de 107 recém-nascidos da Unidade Neonatal. Foram utilizados para cultura de cateter o método semiquantitativo e qualitativo ou método semiquantitativo e quantitativo, e as hemoculturas cultivadas pelo sistema automatizado Bactec. Para a análise fenotípica da similaridade dos isolados de pontas de cateteres e hemoculturas foi utilizado o teste de sensibilidade às drogas antimicrobianas pela técnica da difusão da droga em ágar. Para análise genotípica do perfil de similaridade dos isolados de cateter e hemocultura concomitantes e para o delineamento do perfil clonal das amostras de S. epidermidis isoladas de hemoculturas foram utilizados as técnicas de RAPD-PCR (Random Amplified Polymorphic DNA based PCR) e REP-PCR (Repetitive Extragenic Palindromic Sequence based PCR). Dos 107 recém-nascidos estudados, 45 apresentaram o mesmo microrganismo na ponta de cateter e na hemocultura concomitantemente, desse total 86.7% apresentaram colonização por Staphylococcus coagulase-negativa, 4.4% por Staphylococcus aureus, 4.4% por Candida parapsilosis, 2.2% por Enterococcus faecalis e 2.2% por Pseudomonas aeruginosa. A determinação da similaridade dos isolados revelou que dos 45 recém-nascidos, 46.7% apresentaram infecções da corrente sanguínea relacionadas a cateter pelo método de disco difusão em ágar, 68.9% apresentavam infecções da corrente sanguínea relacionadas a cateter com a utilização da técnica de RAPD-PCR com os primers do grupo...

Catheter-related infections constitute one of the main causes of bacteremia in neonatal ICUs. The aim of the present study was to analyze, by means of molecular typing techniques, the similarity between microorganisms isolated from catheters and blood cultures for the diagnosis of catheter-related bloodstream infection in newborns. The evaluation included 124 catheter tips and 155 concomitant blood cultures from 107 newborns in a Neonatal Unit. For the catheter culture, the semiquantitative and qualitative method or the semiquantitative and quantitative method was used, as well as blood cultures kept by the automated system Bactec. For the phenotypic analysis of similarity between isolates from catheter tips and blood cultures, the test of sensitivity to antimicrobial drugs using the technique of drug diffusion in agar was adopted. For the genotypic analyses of similarity profiles between isolates from catheter and concomitant blood culture and for the clonal profile design of S. epidermidis samples isolated from blood cultures, the techniques RAPD-PCR (Random Amplified Polymorphic DNA-based PCR) and REP-PCR (Repetitive Extragenic Palindromic Sequence-based PCR) were employed. Of the 107 studied newborns, 45 had the same microorganism in the catheter tip and in the blood culture concomitantly; of this total, 86.7% were colonized with coagulase-negative Staphylococcus, 4.4% with Staphylococcus aureus, 4.4% with Candida parapsilosis, 2.2% with Enterococcus faecalis, and 2.2% with Pseudomonas aeruginosa. The assessment of similarity between isolates indicated that, of the 45 newborns, 46.7% had catheter-related bloodstream infections according to the agar disk diffusion method, and 68.9% had catheter-related bloodstream infections according to RAPD-PCR using group-1 primers (RAPD1 for Staphylococcus spp., RAPD 7 for Enterococcus faecalis, ERIC 1 for Pseudomonas aeruginosa, and OPR13... (Complete abstract click electronic acccess below)
Keywords: Cateteres; Infecções neonatais; Sangue - Infecções; Propolis; Stress; Cytokines